School-based professional development in one Lebanese school: how much is too much? - Nabhani, Mona; Bahous, Rima; Hamdan, Zeina (Professional Development in Education, 2012)
This case study examines the attitudes of the secondary and middle school teachers at one school in Lebanon regarding the effect of the school’s professional development (PD) programs on the quality of their teaching practices and motivation. It also examines teachers’ attitudes regarding PD as well as their recommendations to improve the quality of the PD program provided by their school. Questionnaires, focus group interviews and observations were conducted to collect and triangulate data results. Results show that teachers regard PD in their school as beneficial in general but able to be enhanced further. Although the attitude of novice teachers towards PD is more favorable than that of veteran teachers, findings show that the overall teachers’ attitude towards PD is a negative one. Modifications and suggestions to improve the quality of the PD activities are proposed by the teachers. The school offers a prosperous PD program, but its fruitfulness will remain limited unless an organizational structure is created.
Keywords: Lebanon; professional development; schools; ⛔ No DOI found

School-based teachers’ professional development through technology-enhanced learning in Bangladesh - Shohel, M. Mahruf C.; Banks, Frank (Teacher Development, 2012)
To promote significant pedagogical change, the most successful teacher education programmes for the global south happen in the school context. This paper is based on a pre-pilot intervention study of an international education development programme in Bangladesh. Technology-enhanced learning, in this case the use of the Apple® iPod® (iPod touch®), was used to support teachers’ teaching and learning in their school contexts. This paper presents evidence to demonstrate how such school-based technology-enhanced support systems impact on classroom practice and help teachers’ professional development. Using the case of a pre-pilot intervention in the Underprivileged Children’s Educational Programs schools, it explores the teachers’ professional development by analysing interviews with the teachers who were participating in the pre-pilot intervention programme, and draws the conclusion from the collected data that school-based teachers’ professional development through technology-enhanced learning is contributing significantly to in-service training in a resource-constrained context.
Keywords: AUDIOVISUAL education; BANGLADESH; Bangladesh; COMPUTER assisted instruction; ENGLISH language -- Study & teaching -- Foreign speakers; Education--Teaching Methods And Curriculum; Educational technology; LANGUAGE teachers; Learning; PROFESSIONAL education; Professional development; SECONDARY school teachers; TEACHER development; TEACHERS -- Attitudes; Teacher education; UCEP-Bangladesh; __:import:01; __:match:final; __:matched; __:study_id:2099954; ___working_potential_duplicate; hand-held device; school-based; teachers' professional development; teachers’ professional development; technology-enhanced learning

School-based teachers' professional development through technology-enhanced learning in Bangladesh - Mahruf C Shohel, M; Banks, Frank (Teacher Development, 2012)
To promote significant pedagogical change, the most successful teacher education programmes for the global south happen in the school context. This paper is based on a pre-pilot intervention study of an international education development programme in Bangladesh. Technology-enhanced learning, in this case the use of the Apple® iPod® (iPod touch®), was used to support teachers' teaching and learning in their school contexts. This paper presents evidence to demonstrate how such school-based technology-enhanced support systems impact on classroom practice and help teachers' professional development. Using the case of a pre-pilot intervention in the Underprivileged Children's Educational Programs schools, it explores the teachers' professional development by analysing interviews with the teachers who were participating in the pre-pilot intervention programme, and draws the conclusion from the collected data that school-based teachers' professional development through technology-enhanced learning is contributing significantly to in-service training in a resource-constrained context.
Keywords: Bangladesh; Education--Teaching Methods And Curriculum; Educational technology; Learning; Professional development; Teacher education; UCEP-Bangladesh; ___working_potential_duplicate; hand-held device; school-based; teachers' professional development; technology-enhanced learning

A case study of using an online community of practice for teachers' professional development at a secondary school in China - Wang, Qiyun; Lu, Zhiping (Learning, Media and Technology, 2012)
In this case study, an online community was designed at a secondary school in China for the teachers to prepare their lessons collectively, reflect on their teaching practices, collect comments from peers, and share resources. A survey was administered to the teachers to investigate their perceptions on the online community for their professional development. Two hundred and eighty-three teachers responded to the survey and eight teachers were further interviewed by email. The result showed that most teachers liked using the online community as they could gain subject knowledge and could obtain support from peers, share experiences and get feedback, and exchange resources. Also, online entries confirmed that transformational changes in teaching pedagogy and students' learning activities occurred along the time. However, certain teachers did not participate in the online community frequently. This paper describes the context of the case study, design dimensions of the online community, teachers' positive perceptions on using the online community, and transformational changes. Also, strategies for promoting effective use of the online community are discussed and follow-up studies to address the challenges involved in this study are proposed. [PUBLICATION ABSTRACT]
Keywords: Case Studies; China; Communities of Practice; Distance Education; ERIC, Current Index to Journals in Education (CIJE); Education--Teaching Methods And Curriculum; Educational Practices; Electronic Learning; Electronic Mail; Foreign Countries; Interviews; Learning; Lesson Plans; Mail Surveys; Online instruction; Participant Satisfaction; Pedagogy; Polls & surveys; Professional Development; Professional development; Secondary Education; Secondary School Teachers; Secondary school teachers; Teacher Surveys; Teaching Methods; Technology Uses in Education; Transformative Learning; __:import:01; __:match:final; __:matched; __:study_id:2096477; __finaldtb; community of practice; lesson planning; professional development; reflection; technology

Teacher professional development using mobile technologies in a large-scale project: lessons learned from Bangladesh - Shrestha, Prithvi (International Journal of Computer-Assisted Language Learning and Teaching (IJCALLT), 2012)

Online learning community: A case study of teacher professional development in Indonesia - Sari, Eunice (Intercultural Education, 2012)
This paper investigates the concept of online learning community (OLC) to address the issues of teacher professional development practice in twenty-first-century Indonesia. Teachers in Indonesia are trained in a 'conventional way', hence, not ready to prepare the younger generations for entrance into the twenty-first-century complex life and work environment. The pedagogical transformation of a teacher can be facilitated through teacher professional development. Recent studies show that OLC holds great promise in improving teachers' professional practice. This paper presents key results of the introduction and trialling of OLC with Indonesian teachers and teacher educators between 2009 and 2010 and aims to explore the feasibility of this model to support professional development of teachers in this era. The social learning interactions among community members were examined using Scardamalia's Twelve Socio-Cognitive Determinants of Knowledge Building and Hoftsede's Cultural Dimension Review for Indonesia.

Teachers' professional development in a challenging educational context -- a study of actual practice in rural western Kenya - Onguko, Brown (University of Calgary, 2012)
This research adopted a design research approach, utilizing a mixture of methods including narratives, ethnographic observations, qualitative interviews and documentation of design artifacts. It was implemented in a challenging context in Western Kenya. The first research question for this study was: How might professional development (PD), offered through a blended learning approach and delivered by appropriate technologies, inform potential change to teaching practice in a challenging context in Kenya? Research question two sought to understand the implications of the professional development implemented in this study for teachers and professional development teachers (PDTs). Question three sought to understand the sustainability and scalability of the professional development approach The theoretical framework informing this research is based on activity theory- a needs-driven and goal directed process through tool mediation, and entails division of labor and isolation of partial tasks in a community of relationships (Vygotsky, 1978; Leont’ev, 1978; Engestrom, 1987; 1999; 2000; 2008). Key features of activity theory are active engagement and social interaction, which enabled teachers to collaboratively work with each other, studying through appropriate technologies to inform their teaching practices. Based on a review of literature, interviews with teachers and observation of teachers during face-to-face meetings in professional development and in their classroom practice, this study suggests that teachers in a challenging context can inform potential change to their teaching as a result of participation in locally developed content, delivered through blended learning on appropriate technologies. This study observes that through self-directed study on tablets, and occasional face-to-face interaction, teachers can transform into a community of learners that support each other in planning for their lessons. Content development involving local experts is critical to such interventions in challenging contexts, while drawing from global web content, harnessing open educational resources and being sensitive to local culture. Reflective conversations, professional dialogues and technology stewardship were all critical in informing teachers’ practice.
Keywords: __:import:01; __:match:final; __:matched; __:study_id:2457443; __finaldtb; ⛔ No DOI found

Pre-service teacher training in Malawi: findings of a pilot study on the viability of media players for teacher development - Carrier, Carol; Finholt-Daniel, Matt; Sales, Gregory C (International Journal of Education and Development using Information and Communication Technology, 2012)
As part of the United States Agency for International Development (USAID funded Malawi Teacher Professional Development Support project, a sub-task was the piloting of an alternative technology that could be used for improving the quality and consistency of teacher continued professional development (CPD). The pilot, which included 26 open and distance learning (ODL) student teachers, was launched in the spring of 2011 using a low-cost portable MP3 multi-purpose device. A short course on numeracy, containing 5 weekly lessons, was piloted. Each lesson consisted of one or two readings, two videos, and an assignment that directed the learner to complete tasks and document their completion using the camera and audio recorder features of the media player. The viability of using the media player for CPD was evaluated on the ease of use, effectiveness of instruction, and potential for long-term scalability. The evaluation results demonstrated that, with a small amount if initial training, the devices were easy to use and they effectively deliver instruction. Scalability, however, is critical to the long-term success of an initiative based on these or similar devices. An analysis suggests that an affordable option worth considering is the systematic, shared use of media player devices within schools. This approach could dramatically reduce the cost of using this alternative technology for ODL training to pennies per lesson. [PUBLICATION ABSTRACT]
Keywords: Distance learning; Education; Learning; Malawi; Software; Student teachers; Teacher education; Teaching; __:import:01; __:match:final; __:matched; __:study_id:2096523; __finaldtb; ⛔ No DOI found

Using technology for enhancing teaching and learning in Bangladesh: challenges and consequences - Shohel, M. Mahruf C.; Kirkwood, Adrian (Learning, Media and Technology, 2012)
The increasing use of media and technologies for enhancing teaching and learning is an important current trend to overcome the challenges of schooling and teacher training in the changing world. Many countries in the Global South are trying to adopt technologies in their school and teacher training systems to achieve the UN Millennium Development Goals. Though some recent research shows impacts of using technologies for enhancing teaching and learning in technology-poor contexts, no research actually addresses the challenges and difficulties associated with using the technologies in those specific contexts. This article presents interview data derived from secondary schools teachers in Bangladesh, in a context beset with many difficulties associated with technology use. In a pilot project, Apple iPods were introduced in 2009 to explore the challenges and consequences of using technology in schools. The data reveal the implications for the teachers’ professional development when they used the iPod as a multimedia player to access educational resources made available to support teaching and learning. This article has also thrown some light on current debates about using technologies for enhancing teaching and learning in technology-poor contexts.
Keywords: Bangladesh; THEME: Curriculum and resources; THEME: Open systems; THEME: Teacher Professional Development; _Source:Intuitive; teachers’ professional development; teaching and learning; technology; technology-poor contexts; the

New modes of teacher pre-service training and professional support - Anamuah-Mensah, Jophus; Banks, Frank; Moon, Bob; Wolfenden, Freda (Teacher education and the challenge of development: a global analysis, 2012)
Keywords: Economic development -- Effect of education on -- Developing countries.; Teachers -- Training of -- Developing countries.; Teaching -- Developing countries.

Demonstrating a situated learning approach for in-service teacher education in rural India: The Quality Education Programme in Rajasthan - Saigal, Anju (Teaching and Teacher Education, 2012)
Recent educational policy in India has repositioned elementary school teachers as active, reflective practitioners, not just ‘deliverers’ of syllabus material. This article examines innovations in teacher support in Rajasthan's government schools through the ‘Quality Education Program.’ Drawing on qualitative research of collaborative learning processes, the paper discusses two support strategies used by the program: professional dialogic interactions and modeling of pedagogic strategies, which paralleled introductory or developmental phases within a ‘collaborative apprenticeship model’ of teacher professional development. In doing so, the paper outlines the potential of situated, collaborative approaches for Indian in-service teacher education and education development reform, more broadly.

Low Cost Mobile Phones for Large Scale Teacher - Walsh, Christopher S; Shaheen, Robina; Power, Tom; Hedges, Claire; Kahtoon, Masuda; Mondol, Sikander (2012)
Education has the power to transform societies and contribute to social and economic development. In this paper we present the mobile technologies used for teacher professional development (TPD) and communicative language teaching in English in Action (EIA). The project aims to assist 25 million people access greater social and economic opportunities through English language teaching and TPD. EIA, in partnership with the Government of Bangladesh, will work with 80,000 teachers through a work-based programme of TPD using audio and visual resources on low cost mobile phones. With access to over 700 audio files aligned with the national textbook English for Today and professional development films that explain and then illustrate successful student-centred English teaching and learning, the project has already documented significant improvement in teachers’ and pupils’ English language competency. This paper provides an account of, and rationale for, the changes in the technologies used across two phases of the project, from the iPod Nano and Touch used in the pilot study with 690 teachers (2009-2010) to the low cost Nokia C1-01 mobile phone with a micro secure digital (SD) being used in upscaling to 12,500 teachers (2012-2014). We argue the low cost alphanumeric mobile phone with micro SD cards provides unprecedented opportunities to both deliver TPD and improve teachers’ and students’ communicative English language skills. The paper considers the unique suitability mobile phones present for resource constrained education systems in developing countries. Simultaneously we highlight the need for further application and research into the use of mobile technologies, not only for large-scale TPD projects, but for a diversity of international development projects and programmes which aim to achieve sustainable change at scale.

Transforming education for girls in Tanzania and Nigeria: Cross country analysis of endline research studies - Unterhalter, Elaine; Heslop, Jo (ActionAid, 2012)
This cross country summary of the findings from the endline study conducted for the TEGINT project highlights a number of issues of particular pertinence to the community of policy makers, practitioners, and researchers concerned with gender equality, rights and girls’ education. Firstly, the considerable expansion of education provision at primary and junior secondary levels enhances girls’ enrolment, attendance, progression, attainment and empowerment. However, there are regional and locational differences, and the effects of the emergence of private schools on gender equality and girls’ empowerment merits careful scrutiny. It is a matter of concern, that despite the introduction of free primary education, schools continue to charge levies and that the costs of improving education are being passed down to the poorest. Secondly, there are clear indications that girls’ clubs give an important space for girls to learn about their rights and confidence to articulate solutions to their problems. This is the case both when girls in clubs come from higher performing girls in terms of class position and more marginalised girls. Thus girls clubs, widely used in many projects throughout Africa, but not till now well evaluated, appear an important strategy to continue to support. Thirdly, rurality appears as a particular condition of marginalisation, associated with higher levels of gender inequality. This is evident from the lower levels of girls’ empowerment in rural schools, and differences in articulating solutions. Thus particularly engaged interventions are needed with girls in remote areas to support empowerment. Fourthly, while improving teacher qualifications and engagement with gender equality is a necessary condition for enhancing education rights for all children, this is not a standalone intervention, and needs to be supported by other initiatives, possibly associated with teachers’ pay, work conditions and status. Fifthly, an intervention like TEGINT, appears particularly useful in helping to break the silence around gender based violence, however, such an intervention cannot be seen in isolation from work on other aspects of gender inequalities, poverty, and limited social provision. In a country like Tanzania, where there is more legislation and political action around gender equality than in Nigeria, girls, even the poorest, appear more knowledgeable about rights. Gender equality and girls’ education cannot thus be separated from other initiatives on rights, social development and addressing injustice.

Teacher reflections and praxis: a case study of Indian teachers of English as a foreign language - Makarani, Sakilahmed A. R. (University of Hawai'i at Mānoa, 2012)
This case study engaged Gujarati English as Foreign Language (EFL) teachers in video-based reflection with the goal of increasing their reflective abilities and uncovering their understandings about reflective teaching practices in the Indian pedagogical and cultural context. The study aimed to explore, and gain a deeper understanding of how structural, institutional, and social dynamics of the larger socio-political cultural context of India affected the classroom teachers' thinking and their teaching practices. It was hoped that not only would the Gujarati teachers demonstrate an ability to reflect on their practice, but that they would also engage in a critical examination of the factors that impacted their context. The computer-based qualitative data analysis software, Atlas.ti, was used to analyze data using a grounded theoretical approach. The findings indicated that participants successfully engaged in reflection about their teaching using video as the tool for their professional development. Initially teacher participants had mixed feelings about recording and watching videos of their classroom instruction; however, teacher participants later enjoyed the experience, explicitly stating that such reflection helped them. The study also revealed that teacher participants perceived parental, social, institutional, and economic factors as influences on their students' learning, however these were simply identified as problems or conditions without any type of deeper critical analysis. Further, it was found that the teachers did not reach a critical level of reflection, nor did they consider taking action to address fundamental contextual issues. While this study showed that teacher reflection using digital video recordings of classroom practice can be a productive approach to meaningful teacher reflection in India, the study also demonstrated that teachers need specific exposure to deeper critical pedagogical thinking to go beyond simply identifying or blaming the social or economic issues embedded in their context. The study concludes with recommendations on how to reach critical teacher reflection. It is hoped that this case study will add to the growing body of research literature related to teacher self-reflection as a means to improving teaching practice and preparing teachers to take on social challenges in the Indian context. [The dissertation citations contained here are published with the permission of ProQuest LLC. Further reproduction is prohibited without permission. Copies of dissertations may be obtained by Telephone (800) 1-800-521-0600. Web page: http://www.proquest.com/en-US/products/dissertations/individuals.shtml.]
Keywords: Case Studies; Computer Software; Cultural Context; ERIC, Resources in Education (RIE); Economic Factors; English (Second Language); Foreign Countries; Grounded Theory; India; Indians; Language Teachers; Qualitative Research; Reflective Teaching; Second Language Instruction; Second Language Learning; Social Influences; Teacher Attitudes; Teaching Methods; Video Technology; __:import:01; __:match:final; __:matched; __:study_id:2096525; __finaldtb

What professional development makes the most difference to teachers? - Walter, Catherine; Briggs, Jessica (University of Oxford Department of Education, 2012)

A Professional Development Program for the Mother Tongue-Based Teacher: Addressing Teacher Perceptions and Attitudes Towards MTBMLE - Stone, Rebecca J Paulson (University of Massachusetts Amherst, 2012)

The effects of continuing professional development (CPD) though SPRINT on teacher classroom practices and student learning outcomes. In Collaboration toward Greater Autonomy in Educational Development - Mubanga, R (2012)

Using technology for enhancing teaching and learning in Bangladesh: challenges and consequences - Mahruf, C.; Shohel, M.; Kirkwood, Adrian (Learning, Media and Technology, 2012)
Keywords: BANGLADESH; Bangladesh; COMPUTER assisted instruction; COMPUTERS in education; CONTINUING education; DEVELOPING countries; EDUCATIONAL technology; INFORMATION technology; PROFESSIONAL education; SECONDARY school teachers; TEACHER development; TEACHERS -- In-service training; _Source:Intuitive; _THEME: Curriculum and resources; _THEME: Open systems; _THEME: Teacher Professional Development; __:import:01; __:match:final; __:matched; __:study_id:2096535; __finaldtb; teachers’ professional development; teaching and learning; technology; technology-poor contexts; the

Context and Appropriate Technology: The Unavoidable Partnership - Onguko, Brown (2012)
Teachers in rural parts of Kenya lack opportunities for professional development (PD). In addition, the teachers have no access to eLearning opportunities like their colleagues in urban parts. Among the factors that do not favor Kenyan rural teachers’ access to PD through eLearning include: lack of access to relevant technologies and lack of electricity. This paper shares research findings on provision of teachers’ PD through a blended learning approach, utilizing appropriate technologies in a rural school in western Kenya. Ten teachers and two Professional Development Teachers (PDTs) participated in this research. In the study, teachers’ needs assessment was done, to inform the instructional design on the topic: How to teach a large class of mixed ability students. The PD was implemented by engaging teachers in a variety of activities including: pairs of teachers collaboratively using a tablet to access self-study content; teachers studying through multimedia content; teachers planning and delivering lessons using activity-based learning and cooperative learning approaches; and PDTs and teachers participating in fortnightly face-to-face meetings. The findings of the study suggest that teaching practices of rural educators can be improved working with local experts to create locally-relevant content for needs-based PD, implemented in a blended learning approach while providing technology stewardship. Teachers accessed and studied through offline content; planned for and implemented cooperative learning and activity-based learning in lessons, using locally available materials; engaged in reflective conversations on successes and challenges; and spontaneously engaged in very lively professional dialogues. While teachers appreciated that it took long to prepare for active learning lessons, it was less strenuous to implement the lessons, because the students took responsibility for their own learning.
Keywords: __:import:01; __:match:final; __:matched; __:study_id:2096499; __finaldtb; ⛔ No DOI found

Evaluations of situational judgement tests to assess non-academic attributes in selection - Patterson, Fiona; Ashworth, Victoria; Zibarras, Lara; Coan, Philippa; Kerrin, Maire; O’Neill, Paul (Medical Education, 2012)
Medical Education 2012: 46: 850–868 Objectives This paper presents a systematic review of the emerging international research evidence for the use of situational judgement tests (SJTs) for testing important non-academic attributes (such as empathy, integrity and resilience) in selection processes. Methods Several databases (e.g. MEDLINE, PsycINFO, Web of Science) were searched to retrieve empirical studies relating to SJTs published between 1990 and 2010. Personal contact with experts in the field was made to identify any unpublished research or work in progress to obtain the most current material. Finally, reference lists were checked to access other relevant journal articles and further research. All research studies were required to meet specific inclusion criteria selected by two independent reviewers. Results Over 1000 citations were identified during the initial literature search; following the review of abstracts, full-text copies of 76 articles were retrieved and evaluated. A total of 39 articles that adequately met the inclusion criteria were included in the final review. The research evidence shows that, compared with personality and IQ tests, SJTs have good levels of reliability, predictive validity and incremental validity for testing a range of professional attributes, such as empathy and integrity. Conclusions SJTs can be designed to test a broad range of non-academic constructs depending on the selection context. As a relatively low-fidelity assessment, SJTs are a cost-efficient methodology compared with high-fidelity assessments of non-academic attributes, such as those used in objective structured clinical examinations. In general, SJTs are found to demonstrate less adverse impact than IQ tests and are positively received by candidates. Further research is required to explore theoretical developments and the underlying construct validity of SJTs.